Individualism and sensitivity of investment to stock prices: evidence from emerging markets - Amin, Ayatallah Mohamed (AUC Knowledge Fountain, 2015)
Chui et al. (2010) argue that cultures with high levels of individualism are defined by overconfidence and self-attribution bias. Markus and Kitayama (1991) and Heine et al. (1999) note that these biases lead to less efficient stock prices with excess volatility. Foucault and Frésard (2012) show that sensitivity of investment to stock prices is an increasing function of informativeness of stock prices. They argue that sensitivity of investment to stock prices increase because value-maximizing managers are forced to use all available information to forecast the cash flows of their capital allocation decisions. They argue that information revealed via informative stock prices is new to value maximizing managers. Consequently, these managers incorporate this information in their analysis, thereby increasing sensitivity of investment to informative stock prices. This paper argues that individualism, being a significant determinant of information content in stock prices, can also affect sensitivity of investment to stock prices. Using data from 37 emerging markets, our results show that individualism significantly reduces sensitivity of investment to stock prices during the period between 2008 and 2014. Our results are robust to alternate estimation procedures. Our results also indicate that the effect of individualism on sensitivity of investment to stock prices is more pronounced when investment expenditures are large. Moreover, we also show that the impact of individualism on the sensitivity of investment to stock prices is moderated by the institutional, social, and cultural environment of the country.